An Optimized Two-Herb Chinese Food as Medicine Formula Reduces Cisplatin-Induced Nephrotoxicity in the Treatment of Lung Cancer in Mice - Shi, Le; Shu, Yang; Hu, Xiangdong; Akram, Waheed; Wang, Jun; Dong, Shuang; Luo, Biaobiao; Zhang, Jiuliang; Hu, Sheng; Li, Xiaohua; Hu, Xuebo (Frontiers in Pharmacology, 2022)
Chemotherapy is considered a most effective way to treat cancer. However, it is very common that chemotherapy causes unbearable mental and physical side effects to cancer patients, which ultimately reduces the patients’ confidence of overcoming diseases and compromises the treatment of chemotherapy. Cisplatin, a widely used anti-cancer agent for various types of cancers, also damages non-tumor cells and tissues, which are mostly related to the activation of inflammation pathway. Previously, we have discovered that a few rational formula of food as medicine materials reduces systemic inflammation in vitro and in vivo models. Hence, this study reports the ability of an optimized traditional Chinese anti-inflammatory formulation capable to synergize the anti-tumor effect of cisplatin and relieve the kidney damage rather than decrease the anti-tumor effect of cisplatin through the screening of cellular anti-inflammatory models. Our findings suggested that the therapeutic index of cisplatin-based chemotherapy was able to be enhanced by minimizing toxicities from two-herb formula to inhibit the inflammation in mouse tumor models and cisplatin-induced acute kidney injury mouse models.